The white canons of St. Norbert, a history of the Premonstratensian order in the British isles and America, - Kirkfleet, Cornelius James (St. Norbert Abbey, 1943)
The Order of Canons Regular of Prémontré, also known as the Premonstratensians, the Norbertines and, in Britain and Ireland, as the White Canons (from the colour of their habit), are a religious order of Canons regular of the Catholic Church founded in Prémontré near Laon in 1120 by Norbert of Xanten, who later became Archbishop of Magdeburg. Premonstratensians are designated by O.Praem. (Ordo Praemonstratensis) following their name. Norbert was a friend of Bernard of Clairvaux and so was largely influenced by the Cistercian ideals as to both the manner of life and the government of his order. As the Premonstratensians are not monks but Canons Regular, their work often involves preaching and the exercising of pastoral ministry; they frequently serve in parishes close to their abbeys or priories.
Keywords: 🇬🇧 great britain (general); 📚 premonstratensian (general)

Relationes ordinis nostri cum ordine cisterciense - Valvekens, Johannes B. (Analecta Praemonstratensia, 1943)
Keywords: 📚 premonstratensian (general)